EFFECT OF POLYMERIC BLEND ON EX-VIVO PERMEATION STUDIES OF ACECLOFENAC LOADED FILM FORMING GEL - BAJAJ, HIMANI; SINGH, VINOD; SINGH, RANJIT; KUMAR, TIRATH (International Journal of Applied Pharmaceutics, 2021)
Objective: To date, film-forming systems have been intensively investigated for transdermal drug delivery. Film-forming systems offers various advantages compared over conventional transdermal drug delivery systems. The objective of the present study was to study the effect of polymeric blend on ex-vivo permeation studies of topical film-forming gel of aceclofenac. Methods: Film-forming gels were prepared by using Hydroxypropyl methylcellulose and Eudragit polymeric blend in varied concentrations, polyethylene glycol 400 as plasticizer, ethanol as solvent and tween 80 as a penetration enhancer. The prepared film-forming gels were evaluated and the influence of the concentration and ratio of polymeric blends used plasticizer and ethanol were investigated. Results: All the prepared film-forming gels showed satisfactory properties regarding homogeneity, compatibility, viscosity and pH value. Variation in the concentration of polymers showed a variable effect on drug permeation rate from film-forming gels. Almost, all formulations permeated up to 80% of drug in 12 h and formulation F1 showed a maximum release about 97.54 % in 12 h. Conclusion: Film-forming gels of aceclofenac with sustained-release profile were successfully developed and may provide a promising effective formulation which may improve patient compliance.